Ou metodes van die Satan in 'n moderne samelewing - met besondere verwysing na Openbaring 2 en 3 - Grove, A. H. (Faculty of Theology, University of the Free State, 2000)
It is an unequivocal fact that Satan is at work in this world and especially in the church of Christ. At times his methods are crystal clear and at other times, inexplicable, they are not. It is because the devil appears in many guises. According to Matthew 7:15 and 2 Corinthians 11:14 it is not always possible to determine his modus operandi. The purpose of this article is 1. To identify methods used by and explain the way in which Satan operates in order to attack the Christian church in Asia Minor as described in Relevation 2 and 3. 2. To determine the mortal danger as it exist in this day and time. Satan's strategies and methods are diverse and include the following: 1. The lie. 2. The prosecution and oppression of the church. 3. The constant attempt to get the faithful to compromise their faith; to urge them with irresistible power in an insidious way to accept and follow false doctrine. 4. The strategy of violence, in which no compromise is acceptable. It is important to know that neither Satan's name nor his activities are always mentioned. Take for example such messages as those to Sardis and Laodicea. Yet it is clear that his modus operandi can be reconstructed because of the trials and evidence that he leaves behind. Satan is a master at camouflage and subtle covert operations. 5. He uses man's external circumstances such as his longing for earthly possessions and wealth, his self-satisfaction, his search for instant gratification, his smugness and frailty to gain the upper hand, in order to bring about the fall of a congregation.